The role of nt-probnp in assessing the control of decompensated heart failure patients - Shaban, Awf Abdulrahman (2013)
Several studies had emphasised the role of natriuretic peptides (BNP and NT-proBNP) to diagnose, to assess severity and prognosis, and to control heart failure in outpatient settings. However there were very few studies which showed its role in assessing the control of heart failure in hospitalised patients, and its impact on short and intermediate-term outcome. To evaluate the role of NT-proBNP in assessing the control of decompensated heart failure patients, and its association to clinical features, outcome, echocardiographic findings, and electrocardiography. Patients hospitalised with acute decompensated heart failure were enrolled in this prospective cohort study using systematic sampling. Thorough clinical assessment, with symptoms and signs scoring, NTproBNP, transthoracic echocardiogram and electrocardiography were performed at admission and discharge. Endpoint events (heart failure readmission or death) within one month and six months of patient’s discharge were observed. Thirty patients hospitalised with acute decompensated heart failure were enrolled, with mean clinical score of 7.33 (1.47), median NT-proBNP (2470pg/L), and mean ejection fraction (EF) 38.48% (12.52) at admission. Mean admission period was 4.83 day (1.74). On discharge, the mean difference in clinical symptoms and signs was 3.13 (95% CI 2.68-3.57), EF -5.75 (95% CI -8.95, -2.55) and median difference for NT-proBNP was 595 (p value < 0.001) had significantly improved. Despite that, the data analysis showed that these differences are not related to each others (Regression Coefficient 547.14 (95% CI: -54.83, 1149.10), p-value 0.073). Endpoint events (heart failure readmission or death) within one month and within 6 months of patient’s discharge showed that they were not associated with the extent of NT-proBNP difference. However, analysis showed that there were association between both short-term and intermediate-term events with NT-proBNP level at discharge. Cumulative probability of endpoint events of patients with discharge NTproBNP level < 727.5 pg/mL were less likely than those with > 727.5 pg/mL within 6 months from discharge (p-value 0.009). NT-proBNP difference was not correlated with most of the echocardiographic and electrocardiographic variables differences. NT-proBNP level difference was not associated with clinical symptoms and signs response of acute decompensated heart failure. Clinical symptoms and signs were not dependable marker for assessment of heart failure control, and were not sufficient in evaluation of discharge willingness. There was high percent of endpoint events following discharge, and these were related to EF and NT-proBNP discharge level rather than their in-hospital difference. There were no significant correlations between NT-proBNP difference with response of echocardiographic findings or response of electrocardiographic measurements.